A nomogram for predicting contralateral femoral head collapse after unilateral replacement of bilateral femoral head necrosis - Jiabo Zhu; Xin Sun; Liyan Zhang; Haitao Wang; Pengxiang Tang (Scientific Reports, 2025)
Abstract This study aimed to develop and validate a nomogram, which can effectively predict the risk of contralateral asymptomatic femoral head collapse in patients with bilateral osteonecrosis of the femoral head (ONFH), undergoing unilateral total hip arthroplasty (THA). We retrospectively analyzed the clinical data of patients who underwent unilateral THA for bilateral non-traumatic ONFH in our center from 2015 to 2018. A total of 103 patients participated in at least 5 years of follow-up. The patients were randomly divided into a training set (70%) and a validation set (30%). Univariate and multivariate Cox analyses were used to determine the independent risk factors for contralateral femoral head collapse. Based on these factors, a predictive nomogram model for 3, 4, and 5 years after THA was developed, and the model was evaluated using receiver operating characteristic (ROC) curve analysis, area under the curve (AUC), decision curve analysis (DCA), and calibration curves. Among the103 patients, 64 patients (62.1%) experienced contralateral femoral head collapse after surgery. Independent risk factors included Japanese investigation committee (JIC) types C1 and C2, lower limb length difference, CE angle, and Harris hip score (HHS) one month after the primary THA. The AUC, calibration curves, and DCA for the predictive model at 3, 4, and 5 years demonstrated good performance of the nomogram. The predictive nomogram model shows good accuracy and clinical utility. Using this tool, clinicians can accurately judge the collapse of the contralateral asymptomatic femoral head after unilateral THA in patients with bilateral ONFH, and they can formulate individualized treatment plans.